KELUARGA SEBAGAI ECCLESIA DOMESTICA DALAM FAMILIARIS CONSORTIO DAN REFLEKSI TENTANG “GEREJA SEBAGAI KELUARGA” - Laksito, Petrus Canisius Edi (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2022)
The reinvented values of the family after the pandemic should be responded by the faithful of Christ, taking into account christian families as the domestic Church. Reflecting it from the perspective of John Paul II’s Magisterium, this paper wants to discuss such task: first by mentioning the challange of constructing an ecclesiological approach regarding the significancy of the family for the life of the Church; second by anchoring the reflection in the Vatican Council II’s idea of the family as the domestic Church; third, by deepening the discussion using the vision of Pope John Paul II regarding family as the domestic Church, especially from his apostolic exhortation Familiaris Consortio; and fourth by taking some considerations about its ecclesiological implications formulated in the idea of “Family ecclesiology”.